2016
DOI: 10.1182/blood-2015-08-664631
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Jak2 signaling reveals resistance of mouse embryonic hematopoietic stem cells to myeloproliferative disease mutation

Abstract: Key Points• Emerging HSCs require Jak2 and Pi3k signaling for proliferation and survival.• Embryonic HSCs are unaffected by the JAK2V617F mutation.The regulation of hematopoietic stem cell (HSC) emergence during development provides important information about the basic mechanisms of blood stem cell generation, expansion, and migration. We set out to investigate the role that cytokine signaling pathways play in these early processes and show here that the 2 cytokines interleukin 3 and thrombopoietin have the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…A possible limitation of our model is that iPSC-derived hematopoietic stem cells (HSCs) might show different properties compared with the marrow-derived HSCs. Mascarenhas et al revealed that the mouse embryonic HSCs were relatively resistant to JAK2V617F mutation compared with adult HSCs 16 . Consistent with this finding, we found that JAK2V617F expression also showed minor effects on erythropoiesis from human iPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A possible limitation of our model is that iPSC-derived hematopoietic stem cells (HSCs) might show different properties compared with the marrow-derived HSCs. Mascarenhas et al revealed that the mouse embryonic HSCs were relatively resistant to JAK2V617F mutation compared with adult HSCs 16 . Consistent with this finding, we found that JAK2V617F expression also showed minor effects on erythropoiesis from human iPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…How MLL/SET proteins function during the establishment of the haemogenic endothelium and/or early primitive haematopoietic progenitors remains underexplored ( Table 1 ). Given the multi-domain nature of MLL/SET and that foetal blood cells are distinct from their adult counterparts, it is entirely possible that new molecular mechanisms could be found [ 154 , 156 ]. As noted in Table 1 , there is much to learn about the developmental phenotypes of the MLL/SET family.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there will be conservation in the mechanisms derived from CB or ESC towards the molecular processing that is directed when the fusion occurs in vivo, modelling how MLL fusions impact foetal haematopoiesis with relevant timing is essential to uncovering the characteristics of the infant disease. Indeed, foetal HSPCs possess distinct molecular characteristics that are the result of foetal-specific intrinsic and extrinsic factors, and the cell of origin for the disease is known to be a critical determinant towards the resulting pathology [ 131 , 144 , [153] , [154] , [155] , [156] , [157] , [158] ]. Accordingly, identical knock-in models of adult MLL-AF9 and MLL-ENL leukaemia have shown that disease originates more efficiently from different HSPC populations when comparing both fusions, and that MLL-AF9 expression in LT-HSC causes a more aggressive leukaemia as compared to disease derived from GMP [ 157 , 159 ].…”
Section: The Impact Of Mll1 Fusions On Haematopoietic Developmentmentioning
confidence: 99%
“…Moreover, the release of membrane-bound KitL, as an adhesion/survival-promoting molecule for stem cells, depends on IL-3 [ 34 ]. IL-3 acts as a nonspecific proinflammatory cytokine and drives cell proliferation by the JAK/STAT and PI3K/AKT pathways [ 35 – 37 ]. Our results demonstrated that c-Kit + ASCs stimulated IL-3 release both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%